Of wings and wheels : a synthetic study of the biblical cherubim - Wood, Alice, Ph.D (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft ;, 2008)
This study examines the physical form and cultic function of the biblical cherubim. Previous studies of the cherubim have placed too great an emphasis on archaeological and etymological data. This monograph presents a new synthetic study, which prioritises the evidence supplied by the biblical texts. Biblical exegesis, using literary and historical-critical methods, forms the large part of the investigation (Part I). The findings arising from the exegetical discussion provide the basis upon which comparison with etymological and archaeological data is made (Parts II and III). The results sugge.